Bridging the digital divide from the grassroots: The social and economic impact of RT/RW Net in Jabodetabek Urban Periphery - Hendra Gilbert; Prio Utomo; Krist Ade Sudiyono (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2026)
Despite high internet penetration rates, the benefits of digitalization remain unevenly distributed in Indonesia’s densely populated urban areas. This study investigates RT/RW  Net, a community-driven internet network that has emerged as a grassroots response to the digital divide in Jabodetabek. While often viewed primarily through a legal or technical lens, the socio-economic implications of these networks remain under-explored. Using an interpretive phenomenological approach, this study analyzes data from in-depth interviews, observations, and document analysis involving network managers, users, and local community leaders. The findings reveal that residents adopt RT/RW Net primarily due to affordability and flexible payment schemes. Beyond connectivity, these networks function as mechanisms for Community Driven Digital Inclusion (CDDI), fostering social cohesion through "digital gotong royong" and enabling micro-economic activities. However, sustainability is threatened by legal ambiguity and the risk of enforcement actions. The article concludes by recommending a regulatory framework that legitimizes community networks through cooperative licensing models to ensure inclusive digital transformation.